Magnesium use in pre-sowing treatment of spring wheat seeds - Ramazanova Venera (BIO Web of Conferences, 2021)
Studies of different content of magnesium nanoparticles in combination with stabilizers polyvinylpyrrolidone (PVP) and collagen hydrolyzate (GC) on the effect on the growth processes of spring wheat plants were conducted. It was found that the most positive effect on germination was produced by magnesium preparations in the following concentrations Mg 10 mg + PVP with a rate of 5 ml/t, Mg 20 mg + PVP with a rate of 1 ml/t, Mg 10 mg + GC with a rate of 1 ml/t. The initial growth and development of the root was significantly affected by the variant No3 Mg 10 mg + Ag 1 ml + PVP at the rate of 1 ml/t, and the development of the sprout was affected by all magnesium nanosets at the rate of 1 ml/t. When analyzing the assessment of plant development on days 7, 10 and 15, it was found that magnesium preparations with collagen stabilizer (GC) had a positive effect. Treatment with magnesium preparations on vegetative parts of plants, namely daily sprouts determined the effective rate of the preparation of 5 ml and more. The high values were in the variants Mg 20 mg + PVP, Mg 10 mg + Ag 1 ml + GC, where the increase in sprout length was 2.7-2.9 cm, weight 1.0-1.3 g.